2015
DOI: 10.1105/tpc.114.134452
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis Chloroplast Mini-Ribonuclease III Participates in rRNA Maturation and Intron Recycling

Abstract: RNase III proteins recognize double-stranded RNA structures and catalyze endoribonucleolytic cleavages that often regulate gene expression. Here, we characterize the functions of RNC3 and RNC4, two Arabidopsis thaliana chloroplast Mini-RNase III-like enzymes sharing 75% amino acid sequence identity. Whereas rnc3 and rnc4 null mutants have no visible phenotype, rnc3/rnc4 (rnc3/4) double mutants are slightly smaller and chlorotic compared with the wild type. In Bacillus subtilis, the RNase Mini-III is integral t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(71 citation statements)
references
References 76 publications
3
65
0
3
Order By: Relevance
“…These results suggest that the mutant harbors a defect in chloroplast translation. In vivo 35 S pulse-labeling experiments showed that the overall protein biosynthesis rate was dramatically lower in the mutant than in WT (SI Appendix, Fig. S2C), supporting the idea that chloroplast translation was impaired in the mutant.…”
Section: Significancementioning
confidence: 56%
See 3 more Smart Citations
“…These results suggest that the mutant harbors a defect in chloroplast translation. In vivo 35 S pulse-labeling experiments showed that the overall protein biosynthesis rate was dramatically lower in the mutant than in WT (SI Appendix, Fig. S2C), supporting the idea that chloroplast translation was impaired in the mutant.…”
Section: Significancementioning
confidence: 56%
“…Miniribonuclease III a_ppears to cleave the 23S-4.5S precursor to simultaneously produce the mature 5′ end of 23S and the 3′ end of 4.5S (35). The SOT1 cleavage site is located ∼40 nucleotides upstream of the miniribonuclease III cleavage site.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The cRT-PCR method was basically performed as described previously (Zimmer et al, 2012;Hotto et al, 2015). Two and a half micrograms of circularized wild-type, rap-1, and rbf1-1 RNAs were reverse transcribed using SuperScript III with a gene-specific oligo (16S 5# cRT-PCR F1, 5#-CACCCGTCCGC-CACTGGAAACACCA-3#).…”
Section: Crt-pcrmentioning
confidence: 99%